Proteolysis-Targeting Chimera (PROTAC): Is the Technology Looking at the Treatment of Brain Tumors? - Lospinoso Severini, Ludovica; Bufalieri, Francesca; Infante, Paola; Di Marcotullio, Lucia (Frontiers in Cell and Developmental Biology, 2022)
Post-translational modifications need to be tightly controlled to guarantee the accurate localization and activity of proteins. Ubiquitylation, one of the most important post-translational events, is a dynamic process primarily responsible for proteasome-mediated degradation of proteins and is crucial for both normal homeostasis and disease. Alteration in ubiquitylation leads to the upregulation of oncoproteins and/or downregulation of tumor suppressors, thus concurring in tumorigenesis. Proteolysis-targeting chimera (PROTAC) is an innovative strategy that takes advantage by the cell's own Ubiquitin-Proteasome System (UPS). A PROTAC molecule consists of a protein of interest (POI) ligand, an E3 ubiquitin ligase (E3) recruiting ligand, and a linker: upon binding to the POI, the PROTAC recruits E3 inducing ubiquitylation-dependent proteasome degradation of the POI. To date, PROTACs have successfully entered in clinical trials for cancer therapy. Here, we will discuss the advantages and limitations of PROTACs development and safety considerations for their application in clinics. Furthermore, we will review the potential of PROTAC strategy as therapeutic option in brain tumor, focusing on glioblastoma.